Gobernanza anticipatoria y proactividad administrativa: las virtudes de la descentralización - Ricardo Rivero Ortega (Revista Vasca de Administración Pública)
The COVID-19 crisis has revealed the lack of capacity to anticipate of our multilevel governance, due to a slow reaction of central power. A more decentralized and not 'one size fits all' decision-making methodology could have been smarter, as suggested by the state of science of strategic scenario definition.